Jestem (tylko) słabym amerykańskim antyfundacjonalistą (ze Stanleyem Fishem rozmawia Leszek Drong) - Fish, Stanley; Drong, Leszek (Er(r)go. Teoria - Literatura - Kultura, 2004)
Stanley Fish, I Am (Just) a Weak American Antifoundationalist (Leszek Drong talks to Stanley Fish) In an interview with Stanley Fish Leszek Drong discusses his inspiration by French intellectuals and the development of his philosophical views.